1998
DOI: 10.1038/bjc.1998.86
|View full text |Cite
|
Sign up to set email alerts
|

Expression of αv integrins and vitronectin receptor identity in breast cancer cells

Abstract: Summary In the present study we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 21 publications
(20 reference statements)
5
73
0
Order By: Relevance
“…The two cell lines used, MDA-MB-435 and MDA-MB-231, are immortalized human breast cancer cell lines, and both cell lines express high levels of ␣ v ␤ 3 integrin (15,16). All cpAb constructs and control anti-integrin antibody LM609 bound efficiently to these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two cell lines used, MDA-MB-435 and MDA-MB-231, are immortalized human breast cancer cell lines, and both cell lines express high levels of ␣ v ␤ 3 integrin (15,16). All cpAb constructs and control anti-integrin antibody LM609 bound efficiently to these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that low intensity shear stress activates endothelial ELR ϩ CXC chemokine production via a HSPG/␤3- (43,44). Similar to our findings, FAK-induced p38 activation has been observed in cardiac myocytes, where mechanical stretch phosphorylates FAK to generate a binding site for grb2, a scaffolding protein that links FAK to the MAPK pathway (45).…”
Section: Discussionmentioning
confidence: 99%
“…11 These cell lines and their derivatives were grown in OPTI-MEM medium (Invitrogen, Paisley, U.K.) supplemented with 10% fetal calf serum (FCS) without antibiotics.…”
Section: Cell Culture and Rna Transfectionmentioning
confidence: 99%